“Eles só usam o vento”: Impactos socioambientais na instalação de parques eólicos no litoral do Maranhão, nordeste do Brasil - Oliveira, Wellington Romão (2020)
The Environmental Protection Area (APA) of the Rio Preguiças mouth - Pequenos Lençóis/Região Lagunar Adjacente, popularly known as the APA of Pequenos Lençóis, is located between the mouth of the Preguiças river and the Parnaíba river delta, in the state of Maranhão. This type of conservation unit has as its main creation objective the compatibilization of conservation and the "sustainable" use of the natural resources available. There are several projects for the area, but one that has been highlighted by the size of the socio-environmental impacts that have been generated is the implementation of wind farms. From 2015 onwards, a number of wind farms were installed in the municipalities of Paulino Neves and Barreirinhas, which needed a whole infrastructure of access, with the construction of roads, bridges, and power transmission lines. The global discourse of clean energy generation, employment and income generation was used and legitimized throughout the park ideation process. The main objective of the research was to analyze the social and environmental impacts of the installation of wind farms in the APA of Pequenos Lençóis, based on the discourse used. For this, it was based on Political Ecology and Landscape Geoecology, which provided methodological support and guidance to achieve the proposed objectives. We opted for interactivity between qualitative and quantitative data, seeking greater validation of results through a questionnaire using the Likert scale, applied in two periods, in the installation and operation phases of wind farms. In this way, it was possible to understand the installation discourse and the reality in relation to the actors involved. The results showed several conflicts in order to occupy the areas where the parks and traditional communities are located. The main socio-environmental impacts are the occupation of dune fields, the filling of lagoons, the removal of vegetation and changes in fishing and animal husbandry due to restrictions on use and access to the area. In addition to the changes in the landscape, the dissatisfaction with the political process of installation and the promised benefits, especially in terms of job generation, were investigated. Thus, the wind energy scenario in Maranhão is similar to that of other northeastern states, when considering the occupied coastal areas, the traditional populations impacted, and the discourse used and defended in the generation of "clean" energy. The research is pioneering and contributes to the growing national and international literature on wind energy through this case study in the state of Maranhão; it also contributes to our understanding of conflicts in traditional territories in Brazil and points out recommendations for new wind farm installations.